NEUROHUMORAL ASPECTS OF TRIGEMINAL NEURALGIA (Лучшие интеллектуальные исследования, 2025)
Relevance of the topic. Trigeminal neuralgia is the most common and best known type of prosopalgia. In terms of frequency of occurrence, trigeminal neuralgia is second only to facial nerve pathology, accounting for 7-12% of all cases of facial pain. The high incidence of the disease, the intensity of the pain syndrome, the complexity of diagnosis and treatment, especially in outpatient practice, determine the significance of this pathology, both in scientific and practical terms (Vein A.M., 1994-1998; Karlov V.A., Savitskaya O.N., 1980-1990; Yakhno N.N., 1998; Loeser J.D., 1998). Over the past decades, numerous studies have been conducted on various aspects of trigeminal neuralgia, but this problem still has many controversial and unresolved issues related primarily to its main sections - etiology, pathogenesis and principles of therapy. Thus, all pathophysiological components of the pain syndrome remain undisclosed, in particular, there is no consensus on the significance of neurohumoral processes and the role of immunological reactions in the implementation of the algic phenomenon (Grechko V.E., 1990 - 2001; Osipova V.V., 1998; Sweet J., 1999; Mathew N.T., 2002). As a consequence of insufficient study, there is often low efficiency of the treatment, therefore, trigeminal neuralgia is characterized by the formation of chronic and resistant forms of the disease (Luzin M.N., 1990 - 2002; Prithoi R; 1998; Talasko N., 2001).